Structural equation models are modelling tools with many ambiguities: Comments acknowledging the need for caution and humility in their use - Bagozzi, Richard P. (Journal of Consumer Psychology, 2010)
AbstractMy goal is to provide background and perspective on the use and interpretation of structural equation models (SEMs). SEMs are complex procedures with many assumptions, intricacies, and pitfalls. I hope to give a commentary that complements the primers done by Iacobuci and deepen the users' knowledge of the procedures. But I acknowledge that this effort is at best an incomplete introduction into SEMs and cannot do justice to the many issues (and controversies) associated with it.